Application of DEA in international market selection for the export of goods (2017)
This article proposes a methodology to support decision-making to select an international market. To do so, an output-oriented data envelopment analysis (DEA) model is used. This methodology takes into account multiple variables such as import tariffs, logistics costs, the ease of doing business, cultural gaps, the value of imports, GDP per capita, and logistics performance, among others, which are validated with a correlation analysis. The methodology is applied to frozen beef exported from Colombia, and it assesses the efficiency of possible destination countries. Finally, this study concludes that DEA provides easy to apply robust models identifying countries and regions that generate higher benefits to access international markets.